2014
DOI: 10.1111/jvim.12497
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Phosphate Concentration and Osmotic Resistance During Dietary Phosphate Depletion in Dairy Cows

Abstract: BackgroundHypophosphatemia in early lactating dairy cows has been implicated as primary cause for postparturient hemoglobinuria in cattle. Decreased availability of phosphorus has been proposed to reduce adenosine triphosphate synthesis of erythrocytes and thereby reduce osmotic resistance of these cells.Hypothesis/ObjectivesTo study the effect of phosphorus depletion on the phosphate concentration ([Pi]) in plasma and erythrocytes and the osmotic resistance of erythrocytes and to determine the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 13 publications
4
22
0
Order By: Relevance
“…Then an approximately 200 mg muscle biopsy specimen was obtained using the biopsy needle7, put into the sample vial9 which was tightly closed and analyzed for tissue potassium (IDEXX laboratories Germany). Biopsy specimens were kept at room temperature until analyzed similar to studies which have been published recently 18, 19, 20. The analysis was performed within 48 hours of sample collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then an approximately 200 mg muscle biopsy specimen was obtained using the biopsy needle7, put into the sample vial9 which was tightly closed and analyzed for tissue potassium (IDEXX laboratories Germany). Biopsy specimens were kept at room temperature until analyzed similar to studies which have been published recently 18, 19, 20. The analysis was performed within 48 hours of sample collection.…”
Section: Methodsmentioning
confidence: 99%
“…The potassium measurement in blood plasma was performed at the laboratory of the clinics for ruminants using an ISE incorporated in a blood gas analysis device 5. The potassium concentration in tissue and in the erythrocytes were measured by one of the authors (Dr. Anja Müller, Vet Med Labor GmhH, Division of IDEXX Laboratories, Germany) using inductively coupled plasma optical emission spectroscopy (ICP‐OES)13 which has been described previously 18, 19, 20. Dr. Müller was blinded to the origin of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…This can suggest that hypophosphatemia is not the solely responsible for PPH. Grunberg et al (2015) showed that experimental hypophosphatemia alone was not associated with intravascular hemolysis in cattle (Grunberg et al, 2015). In this study, PPH occurred in hypophosphatemic ewes following frozen pasture grazing.…”
Section: Discussionmentioning
confidence: 52%
“…Haemolytic anaemia has been observed in human beings and cows with hypophosphataemia 38 39. However, haemolysis in those cases might be multifactorial and not be reduced to hypophosphataemia 40. Hypophosphataemia may be taken into account as a predisposing factor for developing anaemia, but seems to be an additional finding in the present case.…”
Section: Discussionmentioning
confidence: 63%